HAJJ THROUGH THE SUFI LENS: THE ROLES OF IDRISIYYAH TOUR & TRAVEL AND ITS IMPACT TO THE SOCIETY - Mursalat, Mursalat; Asy'ari, Muhammad (Institut Agama Islam Negeri Metro, 2025)
This study is motivated by the persistent stereotype that Sufism and its followers are withdrawn from worldly affairs and passive in socio-economic engagement. Such perceptions are further reinforced when associated with the pilgrimage of Hajj, often viewed as the pinnacle of individual spirituality. The purpose of this research is to explore how modern Sufi practices, particularly in the context of Hajj, actively promote social movements and engagement in the digital economy. The study employs a descriptive qualitative approach using literature analysis and case studies of Sufi communities that integrate spiritual values with digital economic initiatives and community empowerment, especially in relation to Hajj-related activities. The theoretical framework is based on social movement theory and spiritual economy, focusing on the transformation of Sufis’ roles in contemporary society. The findings reveal that certain Sufi communities are actively developing digital economic ecosystems that support the Hajj, such as sharia-based crowdfunding platforms, spiritually inspired micro-enterprises, and productive zakat and waqf initiatives. These activities demonstrate that Sufis are no longer confined to an exclusive ascetic lifestyle but are evolving into progressive socio-economic actors. The study concludes that contemporary Sufism, through the integration of spiritual values and modern socio-economic practices, successfully challenges ascetic stereotypes and affirms its relevance in the context of Hajj and inclusive community development.